A Review Essay on Isabel Sawhill's Generation Unbound: Drifting into Sex and Parenting without Marriage and Laurence Steinberg's Age of Opportunity: Lessons from the New Science of Adolescence - Aizer, Anna (Journal of Economic Literature, 2017)
Sawhill and Steinberg approach risky behavior among youth from two different angles: Steinberg argues for intervention during the adolescent years to alter behavior in ways that prioritize patience and self-regulation, while Sawhill advocates interventions that mitigate the negative effects of risky behavior. Both argue that disadvantaged youth suffer worse consequences as a result of risky behavior and therefore stand to gain the most from interventions. While the authors develop strong arguments for adolescent interventions, the existing evidence on their effectiveness is less compelling. To reconcile the promise with the reality, I argue that growing up in environments of significant uncertainty reduces the returns to forward-thinking behavior in the daily lives of disadvantaged youths. Interventions to develop adolescent decision-making skills so as to reduce risky behavior will not be effective if they are inconsistent with the incentives generated by a local environment that is often characterized by uncertainty. (JEL J12, J13)